Prevalence and determinants of metabolic syndrome among adults living with HIV on first-line antiretroviral treatment in southern Ethiopia: a cross-sectional study - Agete Tadewos Hirigo; Daniel Yilma; Ayalew Astatkie; Zelalem Debebe (Therapeutic Advances in Chronic Disease)
Background: Antiretroviral therapy (ART) has significantly reduced morbidity and mortality among people living with HIV (PLWH). However, data on the burden of metabolic syndrome (MetS) in sub-Saharan Africa remains limited, particularly following the implementation of universal test-and-treat strategies and the widespread use of integrase inhibitor-based combinations. Objective: This study aimed to determine the prevalence and associated factors of MetS among adults receiving first-line ART in the Hawassa City Administration, southern Ethiopia. Design: A cross-sectional study. Methods: The study was conducted from January 2023 to May 2024, adapting the World Health Organization (WHO) stepwise approach to collect data. All study-relevant data were collected from participants using a pretested structured questionnaire. MetS was defined according to the 2009 harmonized criteria. A binary logistic regression analysis was conducted to identify predictors of MetS, with adjusted odds ratio (aOR) and 95% confidence intervals (CIs). Results: A total of 450 adults participated in the study, of whom 262 (58.2%) were females. The mean (standard deviation) age of the participants was 41.1(±9.7) years. The prevalence of MetS was 36.4% (95% CI: 32.2–41.6), with low high-density lipoprotein (HDL) cholesterol as the most frequent component observed in 368 (81.8%) participants. Age >50 years (aOR: 2.9; 95% CI: 1.4–6.2), alcohol use (aOR: 2.7; 95% CI: 1.2–6.4), body mass index ⩾25 kg/m² (aOR: 3.7; 95% CI: 1.9–7.1), triglyceride/HDL-cholesterol ratio (aOR: 1.5; 95% CI: 1.3–1.7), family history of hypertension (aOR: 2.1; 95% CI: 1.1–3.8), and high waist-height ratio (aOR: 5.4; 95% CI: 1.8–15.9) were significantly associated with MetS. However, dolutegravir-based first-line regimens were not significantly associated with MetS (p=0.482 for DTG initiation, and p=0.34 for switching to DTG). Conclusion: The noticeable prevalence of MetS among PLWH highlights its potential to increase cardiovascular risks. Therefore, routine screening of PLWH for components of MetS is essential to reduce the health risks associated with metabolic disorders. As most of the identified risk factors are modifiable, implementing lifestyle interventions is also imperative.